2018
DOI: 10.1590/2237-6089-2017-0065
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies among caregivers of people with Alzheimer disease: a systematic review

Abstract: Introduction Caregivers of people with Alzheimer disease (PwAD) report significant stress, burden and depression compared to caregivers of people with other dementias, especially when neuropsychiatric symptoms are prominent. Adequate coping strategies can modify the impact of stressful situations and increase the caregivers’ quality of life. Objective To systematically review the different coping strategies used by caregivers of PwAD to manage neuropsychiatric symptoms. Method We carried out electronic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 31 publications
(105 reference statements)
7
68
0
5
Order By: Relevance
“…Researchers have suggested that intervention programs for caregivers should focus on facilitating access to information, teaching constructive coping strategies for dealing with stress, and developing skills that favor a healthier relationship between the caregiver and the elderly care recipient (De Cola et al 2017;Pinto et al 2016;Queluz et al 2018;Queluz et al 2019b;Simonetti and Ferreira 2008) aiming to preserve the caregivers' mental and socioemotional health (Monteiro et al 2018). The ComTato program was developed to include all these components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have suggested that intervention programs for caregivers should focus on facilitating access to information, teaching constructive coping strategies for dealing with stress, and developing skills that favor a healthier relationship between the caregiver and the elderly care recipient (De Cola et al 2017;Pinto et al 2016;Queluz et al 2018;Queluz et al 2019b;Simonetti and Ferreira 2008) aiming to preserve the caregivers' mental and socioemotional health (Monteiro et al 2018). The ComTato program was developed to include all these components.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, the ability to use constructive coping strategies to adapt to new demands is one of the strongest predictors of mental and socioemotional health for people of all ages (Gilhooly et al 2016;Monteiro, Santos, Kimura, Baptista and Dourado, 2018). For those caring for an elderly relative with health problems, being able to cope positively with the many problems that arise and being able to count on other people to play a supportive role are essential to maintaining their overall wellbeing (Ximenes 2018).…”
Section: Skills That Help Caregivers Adaptmentioning
confidence: 99%
“…64 Others proved that emotion-focused (e.g., accepting, optimism, seeking emotional support) and problem-focused (e. g., planning, seeking medical support) coping strategies were positively correlated with HrQoL of patients and their caregivers. [65][66][67] Finally, continued and regular follow-up and multidisciplinary medical support play an essential role in improving the HrQoL of patients. It is well recognized that fecal incontinence, soiling, and constipation are short-and long-term issues in patients with ARM/HD, which significantly alter HrQoL.…”
Section: How To Improve Hrqol In Arm/hdmentioning
confidence: 99%
“…21,25 In patients with AD, family variables and coping strategies have been shown to affect QOL, providing a protective effect for patients and their caregivers. 23,26,27 Therefore, it is important to assess whether family variables and coping strategies play a moderator role in patients with AD.…”
Section: Introductionmentioning
confidence: 99%